Development of Komipa Media to Improve Students Scientific Thinking at MIS Al-Musthafawiyah - Siregar, Nurul Rizki Amalia; Anas, Nirwana; Lubis, Ramadan (Pusdikra-Publishing.com, 2024)
The research entitled